Constraints on unrest in the Tolbachik volcanic zone in Kamchatka prior the 2012–13 flank fissure eruption of Plosky Tolbachik volcano from local seismicity and GPS data - Kugaenko Yulia; Titkov Nikolay; Saltykov Vadim (My University, 2015)
Abstract A new fissure eruption began on 27 November 2012 on the southern slope of Plosky Tolbachik volcano, which is located in central Kamchatka, Russia, and is part of the Klyuchevskoy volcano group. We analyzed the displacement of the earth surface and the seismicity during several months before the eruption onset. According to seismic and GPS data the eruption was preceded by about 4–5 months (July–November 2012) of synchronous crustal deformation and seismicity. The seismic anomaly comprises low energy level seismicity (mainly M = 1.2–2.3) under Plosky Tolbachik volcano at a depth of less than 5 km. In the 2–3 weeks immediately preceding the eruption the rate of seismicity and the amount of radiated seismic energy exceeded the long-term average values (2000–2011) by more than 40 times. The deformation anomaly was recorded by displacement of the GPS points at distances from 20 to 60 km to the north of Tolbachik. The principal axis of the compressive strain was approximately directed towards the Tolbachik eruption site. The permanent GPS network detected radial compression and tangential stretching. The compressive strain reached about 10− 7 prior to eruption onset. The comparable duration of seismic and deformation anomalies (~ 4–5 months before the eruption) is consistent with a common origin, connected to magma rising from depth, and is interpreted as indicating that they were medium-term precursors to the eruption. Data recorded during this unrest episode of the Tolbachik volcanic zone will contribute to understanding of the reawakening of volcanic activity in this region and others worldwide with similar characteristics.
Keywords: 37.31.19 Сейсмология; Плоский Толбачик; Tolbachik; Kamchatka